Lesões molusco-símiles em paciente com esporotricose Molluscum-like lesions in a patient with sporotrichosis - Regina Casz Schechtman; Giselly Silva Neto De Crignis; Mercedes Prates Pockstaller; Luna Azulay-Abulafia; Leonardo Pereira Quintella; Márcia Belo (Sociedade Brasileira de Dermatologia, 2011)
Esporotricose é uma infecção fúngica subcutânea, adquirida por inoculação direta, causada pelo Sporothrix schenckii. Embora a apresentação clássica linfocutânea represente a maioria dos casos, as formas clínicas atípicas e graves têm aumentado em ocorrência. Esporotricose sistêmica e esporotricose cutânea disseminada são variantes raras, usualmente associadas à imunodeficiência celular ou a estados debilitantes. Relatamos o primeiro caso na literatura de lesões molusco-símiles em esporotricose cutaneomucosa múltipla. Os exames micológico direto e histopatológico apresentavam-se ricos em células leveduriformes. Sporotrichosis is a subcutaneous fungal infection caused by Sporothrix schenckii and acquired by direct inoculation. Although the majority of cases consist of the classic lymphocutaneous presentation, the frequency of atypical and severe clinical forms of the disease has increased progressively. Systemic and disseminated cutaneous sporotrichosis constitute rare variants and such cases are generally associated with cellular immunodeficiency or debilitated states. The present paper describes the first published case of molluscum-like lesions in disseminated mucocutaneous sporotrichosis. Direct mycological examination and histopathology revealed numerous yeast cells.